RENCANA AKSI BADAN PENGELOLA KAWASAN GEOPARK KABUPATEN NATUNA DALAM PENGEMBANGAN PARIWISATA MENUJU UNESCO GLOBAL GEOPARK (UGGp) - Mustajadli Mustajadli; Junriana Junriana (Governance, 2023)
The Natuna Islands will be proposed as a UNESCO geopark site through a Letter Of Intent (LOL) that Indonesia will submit to the UN organization at the end of 2019, which is submitted by the Head of the Agency for the Study and Policy Development (BPPK) of the Ministry of Foreign Affairs. The purpose of this study is to see and find out the Action Plan from BPKGN as the authorized agency which is planned in geopark management to improve the status of the Natuna National geopark to become a UNESCO Global Geopark. The research uses qualitative research methods which aim to put more emphasis on the process and meaning by describing something. This research is descriptive, namely to describe the reality of the events studied by using a sampling technique, namely Purposive Sampling. His research is based on the reference of Presidential Regulation which describes 2 planning dimensions, namely implementing guidelines and amenities. From the results of the analysis, it can be concluded from the findings that it can be explained that from the dimensions of the Implementing Guidelines, it is found that there are still many findings from the Planned Action Plan. This is due to the weakness in the budget sector which still relies on CSR funds. Furthermore, in its implementation, the majority still involve district government structural officials so that in managing geoparks there is no focus, in determining the delineation boundary it is not yet specific in each existing geosite, land status is still unclear, because it is still community property, and there is no Masterplan so that it still relies on action plans. regions and the lack of education about geoparks, so there is a need for socialization about the existence of geoparks. Furthermore, in the Amenity dimension, there are still many incomplete ones, only the sandstone geosite is complete, and the majority of cooperation partners still rely on local communities.